Pleural effusion metastatic papillary thyroid carcinoma with dedifferentiation: a case report and review of the literature - Xu, Jialing; Huang, Bin; Ruan, Huajuan (Frontiers in Oncology, 2025)
Pleural effusion metastatic papillary thyroid carcinoma with dedifferentiation is a rare clinical presentation. We present the case of a 78-year-old female patient who developed chest tightness, shortness of breath, and cough without an obvious cause over the past two weeks. Chest computed tomography (CT) revealed consolidation of the right lung with massive pleural effusion. Cytological examination of pleural effusion revealed malignant tumor cells. Cell wax block analysis showed that the tumor was a nested, papillary, and single-cell structure, and epithelioid cell atypia was obvious. Nuclear grooves or intranuclear pseudoinclusion bodies were not observed. Immunohistochemical results were negative for thyroglobulin (TG) and thyroid transcription factor 1 (TTF-1), partially positive for paired box gene 8 antigen(PAX-8), and a Ki-67 proliferation index of 30%. Further immunohistochemical tests were positive for Braf-V600E and Ber-EP4, and the thyroglobulin serologic test was 265.90 µg/mL. The patient had undergone cervical lymph node dissection for right papillary thyroid cancer 21 years ago, developed lung metastases 4 years ago, and received targeted therapy. This case reminds us that metastatic pleural effusion tumors with atypical pathological morphology and immunohistochemical expression should be comprehensively evaluated in combination with clinical, immunohistochemical, and serological tests, which may help in the diagnosis and treatment of clinicians and pathologists.